1973
DOI: 10.1037/h0033971
|View full text |Cite
|
Sign up to set email alerts
|

Development of two letter-sound patterns in grades one through three.

Abstract: Tests for four letter-sound generalizations, c -» [k], c -» [s], a -> [se], and a-* [e], were given to 73 first-, second-and third-grade children at 6-week intervals during a single school year. Each test included five synthetic words (e.g., cipe, acim, bice, cib, ocet) for each generalization. Children responded individually to the test items by attempting to pronounce each one aloud. The long and short pronunciations of a ([e] and [SB]) and the [k] pronunciation of c were learned to a high degree of accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…); in all other positions k corresponds to /W). These complex and specific rules are acquired gradually and different rules are acquired at different stages of reading (Calfee, Venezky and Champman, 1969;Venezky and Johnson, 1973). Perhaps this ability to learn symbol-sound rules limits the development of reading.…”
Section: Visual-verbal Cross-modal Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…); in all other positions k corresponds to /W). These complex and specific rules are acquired gradually and different rules are acquired at different stages of reading (Calfee, Venezky and Champman, 1969;Venezky and Johnson, 1973). Perhaps this ability to learn symbol-sound rules limits the development of reading.…”
Section: Visual-verbal Cross-modal Mappingmentioning
confidence: 99%
“…There is certainly an association between reading ability and ability to learn sound-symbol correspondences (Birch and Belmont, 1965;Done and Miles, 1978;Venezky and Johnson, 1973), but correlational studies such as these leave causality indeterminate and it is quite likely that those progressing in reading are concomitantly picking up these associations (indeed this notion is implicit in theories of analogical pronunication-the more lexical entries, the more analogues). Training studies (Bishop, 1964;Jeffrey and Samuels, 1967) have shown that detailed training on specific grapheme-phoneme correspondences does improve ability in reading new words.…”
Section: Visual-verbal Cross-modal Mappingmentioning
confidence: 99%
“…Several studies (e.g., Calfee, Venezky, & Chapman, 1969;Perfetti & Hogaboam, 1975;Shankweiler & Liberman, 1972;Venezky, 1976;Venezky & Johnson, 1972) have investigated children's ability to pronounce pseudowords as a means of assessingchildren's knowledge of spelling-sound correspondences. In general, these studies have shown that children do abstract information relating spelling and sound in English in the course of learning to read, and that they learn the simple correspondences between letters and sounds before they learn more complex relations.…”
mentioning
confidence: 99%
“…To call the "silent letter e" in rice a front vowel seems awkward. In contrast, Venezky and Johnson (1973) and Cox (1984) chose to describe only the letter environment. Thus, the letter c receives an/s/pronounciation before the letters e, i, or y.…”
Section: The Letter C and Its Pronunciationmentioning
confidence: 95%